Anticoagulation vs Antiplatelet Treatment in Patients with Carotid and Vertebral Artery Dissection: A Study of 370 Patients and Literature Review. Issue 3 (3rd February 2017) - Daou, Badih; Hammer, Christine; Mouchtouris, Nikolaos; Starke, Robert M.; Koduri, Sravanthi; Yang, Steven; Jabbour, Pascal; Rosenwasser, Robert; Tjoumakaris, Stavropoula
Abstract: BACKGROUND: Dissection of the carotid and vertebral arteries is an important cause of stroke in young patients. OBJECTIVE: The objective of this study is to compare antithrombotic treatments in patients with carotid and vertebral dissections. METHODS: Three hundred seventy patients with carotid and vertebral artery dissections were included. Univariate and multivariate analyses were conducted to analyze the association between treatment and new or recurrent events and clinical outcome. RESULTS: Mean follow-up was 24.3 months. In patients with spontaneous dissection, 55% received antiplatelets, 29.4% anticoagulation, and 12.6% combined treatment. New or recurrent ischemic and hemorrhagic events occurred in 9.6% of patients on antiplatelets, 10.4% on anticoagulation, and 13.3% on combined treatment. For traumatic dissection, 58.3% received antiplatelets, 26.9% anticoagulation, and 10.2% combined treatment. New or recurrent ischemic and hemorrhagic events occurred in 6.9% on antiplatelets, 11.1% on anticoagulation, and 20% on combined treatment. In patients with intracranial dissection, 63.1% were started on antiplatelets, 19.7% on anticoagulation, and 14.5% on combined treatment. Ischemic and hemorrhagic events occurred in 8.5% on antiplatelet treatment, 15.4% on anticoagulation, and 18.2% on combined treatment. In patients with extracranial dissection, 54.4% were on antiplatelets, 28.9% on anticoagulation, and 11.2% on combined treatment. Ischemic and hemorrhagic events occurred in 10.1% on antiplatelet treatment, 9.3% on anticoagulation, and 13.8% on combined treatment. The association between antithrombotic treatment and ischemic/hemorrhagic events and clinical outcome was not significant for all subtypes of dissection. CONCLUSION: The rate of new or recurrent events is similar with antiplatelet and anticoagulation treatment in treating intracranial and extracranial carotid and vertebral artery dissection.